Factors Affecting Non-performing Loans of Nepalese Commercial Banks: A Perception of Bankers - Pant, Dinesh Kumar (Journal of Nepalese Management and Research, 2023)
This study investigated the factors influencing non-performing loans (NPLs) in Nepalese Commercial Banks. Macro-economic factors, managerial efficiency, and lending policy were identified as independent variables, while non-performing loans constituted the dependent variable. A descriptive and causal-comparative research design was adopted to run the study. The population of the study was the entire bankers working at the various branches and province-level offices of the different commercial banks of Karnali province. A convenience sampling plan was used to collect the responses. The data was collected from 406 respondents using a structural questionnaire and analyzed and interpreted through t-tests, correlation and regression analysis using SPSS software. The study concluded that the macroeconomic factors and managerial efficiency, along with lending policy, have a significant impact on the non-performing loans of the Nepalese commercial banks.